Regulator of sex-limitation (Rsl) encodes a pair of KRAB zinc-finger genes that control sexually dimorphic liver gene expression - Krebs, Christopher J. (Cold Spring Harbor Laboratory Press, 2003)
Sexually dimorphic expression of a broad array of liver proteins involved in reproduction and xenobiotic metabolism is induced at puberty by sex-specific growth hormone patterns. An additional control of sex-dependent gene expression is conferred by Regulator of sex-limitation (Rsl) alleles. In variant rsl mice, females inappropriately express the male Sex-limited protein, Slp. We recently showed that a panel of male-specific liver genes is repressed by Rsl, accentuating sex differences in a hormone-independent manner. Here we map rsl to a region on Chromosome 13 comprised exclusively of KRAB (Kruppel-associated box) zinc-finger protein (ZFP) genes. Among eight Rsl candidate (Rslcan) genes within the critical genetic interval, the recent duplicates Rslcan-4 and Rslcan-9 both harbor mutations in rsl mice (partial deletion and splice-site inactivation, respectively). Transgenesis with bacterial artificial chromosome (BAC) clones encompassing Rslcan-4 restores male-specific MUP (major urinary protein) expression to rsl mice, whereas a BAC containing Rslcan-9 rescues sex-specific expression of Slp and cytochrome P450 Cyp2d9. Thus, the Rslcan-4 and Rslcan-9 paralogs partitioned regulation of their target genes during evolution. This demonstrates the first biological role for a set of KRAB zinc-finger repressor proteins and reveals the molecular basis of a gene-silencing pathway critical for sexual dimorphism.